Roles of the WWOX in pathogenesis and endocrine therapy of breast cancer. (March 2015) - Li, Juan; Liu, Jie; Ren, Yu; Liu, Peijun
Breast cancer is one of the most common malignancies, often with complicated etiology and poor clinical outcome. In recent years, a critical role has emerged for the WW domain-containing oxidoreductase (WWOX) in breast cancer. WWOX is a tumor suppressor; it is deleted or attenuated in 29–63.2% of breast cancer tissues and is associated with a poor prognosis of breast cancer patients. WWOX heterozygous knockout mice show a higher incidence of mammary tumors and impaired branching morphogenesis. At the molecular level, WWOX interacts with AP2γ, ErbB4, SMAD3, and WBP2 suppressing their transcription activities in breast cancer cell lines. This review provides comprehensive insights into the current knowledge of WWOX activities in the pathogenesis and endocrine therapy of breast cancer.